2014
DOI: 10.1007/s13593-014-0219-4
|View full text |Cite
|
Sign up to set email alerts
|

Control of tomato whiteflies using the confusion effect of plant odours

Abstract: Glasshouse tomato production is reduced by the whitefly Trialeurodes vaporariorum, a major worldwide pest of glasshouse crops. Whitefly control is achieved using pesticides or parasitoids, which have drawbacks. There is thus a need for other control methods. For instance, the use of volatile compounds from plant odours could profoundly change the behaviour of plant-eating insects. This practice should be safe because plant odours are usually harmless to humans. Therefore, we have studied the effect of plant vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…also showed that coriander ( Coriandrum sativum ) volatiles masked tomato volatiles in host plant selection. Tosh and Brogan also put forward the idea of supplying whiteflies with a superabundance of volatiles to confuse this generalist insect. In conclusion, this study identified volatile candidates that may be emitted by companion plants or by diffusers, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…also showed that coriander ( Coriandrum sativum ) volatiles masked tomato volatiles in host plant selection. Tosh and Brogan also put forward the idea of supplying whiteflies with a superabundance of volatiles to confuse this generalist insect. In conclusion, this study identified volatile candidates that may be emitted by companion plants or by diffusers, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the feeding behaviour of whitefly on S. lycopersicum Mill., 'Elegance' and L. pimpinellifolium, the electrical penetration graph (EPG) technique was used, as developed by Tjallingii (1978) and used previously to investigate whitefly feeding behaviour on tomato (Tosh and Brogan 2015;Lei et al 1997Lei et al , 1999Lei et al , 2001. The different waveforms produced by the completion of a partial electrical circuit between the plant and the whitefly's stylet when the whitefly probes the plant correspond to different feeding behaviours of the whitefly.…”
Section: Electrical Penetration Graph Studiesmentioning
confidence: 99%
“…An eight-channel DC EPG system supplied by EPG Systems (EPG-Systems, Dillenburg 12, 6703 CJ Wageningen, the Netherlands, http://www.epgsystems.eu/ contact.htm; Tjallingii (1978)) was used. Tosh and Brogan (2015) developed a modified EPG apparatus (Fig. 2b, c) to monitor whitefly feeding under different conditions, and here, the same experimental set-up and method for the EPG data collection were used for both tomato species.…”
Section: Electrical Penetration Graph Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Plant volatiles play important roles in locating hosts by guiding the insects to food sources and oviposition sites (Bruce et al, 2005;Bruce & Pickett, 2011;Knolhoff & Heckel, 2014;Tosh & Brogan, 2015). Plant volatiles exhibit an immense diversity, both quantitatively and qualitatively, which allows herbivores to distinguish suitable hosts (Dudareva et al, 2006;Beyaert & Hilker, 2014).…”
Section: Introductionmentioning
confidence: 99%